Analisis Efektivitas Pengendalian Internal terhadap Kredit Macet pada Program KUR di PT. BRI Unit Moyo Hulu - Rizky Kamula; Ahmad Jibrail (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the effectiveness of the internal control system in preventing and managing bad credit within the Kredit Usaha Rakyat (KUR) program at PT. BRI Unit Moyo Hulu for the period 2024–2026. Data were collected through in-depth interviews with the Unit Head, Account Officer (AO), Customer Service (CS), and official credit documents. The results show that internal control procedures have been implemented according to standards, covering SLIK OJK checks, field surveys, clear division of tasks, daily monitoring, and biannual internal audits. Effectiveness was evaluated using the five components of the COSO framework. However, the Non-Performing Loan (NPL) ratio rose from 6.56% in 2024 to 10.16% in 2025 and 10.23% for January–May 2026. This increase was mainly caused by seasonal factors before the harvest season and the use of funds for non-business purposes. Nevertheless, informants considered the internal control system highly optimal because it successfully mitigated risks through credit restructuring and customer education. The study concludes that internal control is procedurally effective, but requires stronger seasonal risk mitigation to further reduce the NPL ratio. In particular, the Risk Assessment component needs to be strengthened by integrating agricultural seasonal cycles and harvest-period risk indicators into the debtor eligibility analysis framework, so that pre-harvest payment default can be anticipated and mitigated more effectively.